Consolidation Of Clay From Sukodono By Adding Stabilization Material With Wood Charcoal Powder - Jarwanto, Jarwanto, Ir. Renaningsih, MT (2017)
Soil sukodono is clay with LL: 85,73%,PL: 24,69%,PI: 61,04% (Prasetyo 2016). The main problem on soil is the soil condition is less stable (expansive soil) so this soil is necessary for soil improvement. Soil improvement is carried out by chemical soil stabilization usin wood charcoal powder with percentage 10%, 15%,and 20%. The result of the physical properties of the native soil and the mixture obtained plastic limit value has increase, while the water content, specific gravity , liquid limit, plasticity index, shinkage limit, and sieve 200 percent decline. The soil mixture classification of 10% and 15% charcoal powder included the A-7-6, 20% group A-7-5. Soil mixture of wood charcoal powder 10%,15%,and 20% according to USCS system including CH group. The result of test mechanical properties from standart proctor test with mixture wood charcoal powder10%,15%,and 20% decrease value of volume weight and increase of optimum water content. The maximum weight value of the volume is 1,182 gr/cm3 and the highest optimum water content is 38% in the addition of percentage 20% wood charcoal powder.In the consolidation test the value of the consolidation coefficient (Cv) increased as the addition of stabilization materials. At compression index value (Cc) as addition of stabilization material the value of Cc decreases. And for the value of settlementconsolidation (Sc) decreased with addition of stabilization materials. Of the soil stabilization variation in the percentage of added wood charcoal powdered, obtained the percentage of a change in value Cv , Cc , and Sc against native soil.Thus the addition stabilization of wood charcoal powder on soil in sukodono district of sragen regency has improved the mechanical characteristic.